Testosterone Exposure During Fetal Masculinization Programming Window Determines the Kidney Size in Adult Mice - Junnila, Arttu; Rytkönen, Kalle T.; Martinez‐Nieto, Guillermo; Perk, Mats; Mäkelä, Otto; Li, Hao; Airaksinen, Jenni; Hyötyläinen, Ida; Mehtovuori, Oliver; Laiho, Asta; Ohlsson, Claes; Elo, Laura L.; et al. (Wiley, 2026)
Kidney size is sex-dimorphic and regulated by androgens in adult humans and mice. However, the effects of developmental androgen deficiency on kidneys remain elusive. We hypothesized that androgens program future kidney growth during fetal development. Male mice lacking the main testosterone-producing enzyme HSD17B3 had reduced testosterone at embryonic day 15.5, but the concentrations increased by E18.5, creating a short time window of androgen deficiency resulting in reduced kidney size in adult males. In male Hsd17b3−/− kidneys, nephron development was qualitatively normal, but the number of glomeruli and proliferation of proximal tubules were reduced, as was proximal tubule size in adults. Testosterone supplementation at E14.5–17.5 normalized the renal size in adult Hsd17b3−/− males. Our data suggest that androgen receptor and HNF4A jointly regulate IGFBP5, putatively influencing FOXO1 and mTOR signaling to promote male-specific kidney growth in the fetal period. In conclusion, we have identified a novel developmental programming effect on male kidneys, where fetal androgen deficiency reduces kidney growth and androgen responsiveness in adult males.